The Impact of Workload and Career Development with Compensation as an Intervening Variable on Employee Performance (Study at PT. SAIMINDONE) - Sofwah U Wusqo; M. Ali Iqbal (PT FORMOSA CENDEKIA GLOBAL, 2023)
The purpose of this study is to analyze the impact of Career Development, Workload on Employee Performance with Compensation as a variable intervening. This study uses quantitative methods. The sample are taken from 152 respondents from the head office in Jakarta. Sources of data in this research using primary data obtained straight from the responders' staff. In order to investigate the relationship between employee performance, workload, and career development, the data analysis method used in this study was multivariate analysis, specifically by using the Partial Last Square (PLS) equation model and the Structural Equation Model (SEM). The results of the study demonstrate that workload has a positive and significant impact on compensation, career development has no significant impact, employee performance is positively and significantly impacted by workload, while career development has no discernible effect. Additionally, employee performance is positively and significantly impacted by compensation, which also partially mediates the relationship between workload and performance.